PI3K, Rho, and ROCK play a key role in hypoxia-induced ATP release and ATP-stimulated angiogenic responses in pulmonary artery vasa vasorum endothelial cells - Woodward, Heather N. (American Physiological Society, 2009)
We recently reported that vasa vasorum expansion occurs in the pulmonary artery (PA) adventitia of chronically hypoxic animals and that extracellular ATP is a pro-angiogenic factor for isolated vasa vasorum endothelial cells (VVEC). However, the sources of extracellular ATP in the PA vascular wall, as well as the molecular mechanisms underlying its release, remain elusive. Studies were undertaken to explore whether VVEC release ATP in response to hypoxia and to determine signaling pathways involved in this process. We found that hypoxia (1–3% O(2)) resulted in time- and O(2)-dependent ATP release from VVEC. Preincubation with the inhibitors of vesicular transport (monensin, brefeldin A, and N-ethylmaleimide) significantly decreased ATP accumulation in the VVEC conditioned media, suggesting that hypoxia-induced ATP release occurs through vesicular exocytosis. Additionally, both hypoxia and exogenously added ATP resulted in the activation of PI3K and accumulation of GTP-bound RhoA in a time-dependent manner. Pharmacological inhibition of PI3K and ROCK or knockout of RhoA by small interfering RNA significantly abolished hypoxia-induced ATP release from VVEC. Moreover, RhoA and ROCK play a critical role in ATP-induced increases in VVEC DNA synthesis, migration, and tube formation, indicating a functional contribution of PI3K, Rho, and ROCK to both the autocrine mechanism of ATP release and ATP-mediated angiogenic activation of VVEC. Taken together, our findings provide novel evidence for the signaling mechanisms that link hypoxia-induced increases in extracellular ATP and vasa vasorum expansion.